(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Surgical procedures stimulate patient’s haemodynamic system and bring about significant clinical changes in heart rate (H. R) and systolic blood pressure (SBP). These variables can be used to assess depth of anesthesia. Tachycardia is strongly linked to sympathetic stimulation along with concomitant rise in blood pressure and may cause decompensation in patients with heart failure. Various drugs are used to control likelihood of these responses by use of anaelgesics. This study was conducted to compare haemodynamic response with two doses of Ketamine to surgical incision. Material and Methods: Sixty Patients were randomly divided into two groups using random numbers table. Group A received ketamine 0.25 mg/Kg whereas group B received ketamine 0.5mg/kg. After setting up the monitors, first value of HR and SBP were taken as baseline value. Propofol 1% in a dose of 2 mg/kg and rocuronium in a dose of 0.6 mg/kg were given I/V for induction in both groups and maintained on sevoflurane. Intravenous ketamine was given according to the assigned group.HR and SBP were recorded before induction as the baseline values, before the administration of ketamine, every minute after ketamine till the surgical incision (SI) and the following five minutes; then at ten and twenty minutes after SI. Percentage change in HR and SBP from the baseline will be calculated for all the readings following administration of ketamine. Results: The results of present study showed that both groups were comparable regarding hemodynamic response after ketamine at 1,2,3,4 and 5 min and their hemodynamic responses were also comparable at 1,2,3,4,5,10 and 20 min after SI. Hemodynamic response to SI was decreased in both groups but there was no statistically significant difference between the two groups. Conclusion: There is no statistically significant difference in both doses of ketamine (0.25mg/kg and 0.50mg/kg) to blunt the haemodynamic response to surgical incision, so lower dose (0.25mg/kg) of Ketamine can be used to avoid the side effects associated with higher doses of ketamine.